En Bloc Resection for Bladder Tumors: An Updated Systematic Review and Meta-Analysis of Its Differential Effect on Safety, Recurrence and Histopathology. Issue 4 (21st April 2022) - Yanagisawa, Takafumi; Mori, Keiichiro; Motlagh, Reza Sari; Kawada, Tatsushi; Mostafaei, Hadi; Quhal, Fahad; Laukhtina, Ekaterina; Rajwa, Pawel; Aydh, Abdulmajeed; König, Frederik; Pallauf, Maximilian; Pradere, Benjamin; et al.
Abstract : Purpose: En bloc resection for bladder tumors has been developed to overcome shortcomings of conventional transurethral resection of bladder tumors with regard to safety, pathological evaluation and oncologic outcomes. However, the potential benefits and utility compared to conventional transurethral resection of bladder tumors have not been conclusively demonstrated. We aimed to update the current evidence with focus on the pathological benefits of en bloc resection for nonmuscle-invasive bladder cancer. Materials and Methods: The PubMed®, Web of Science™ and Scopus® databases were searched in August 2021 according to the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) statement. Studies were deemed eligible if they compared safety, and pathological and clinical outcomes in patients who underwent en bloc resection with conventional transurethral resection of bladder tumors. Results: Overall, 29 studies comprising 4, 484 patients were eligible for this meta-analysis. Among 13 randomized controlled trials, the pooled 12- and 24-month recurrence risk ratios were not statistically different between the 2 surgical techniques (0.96, 95% CI 0.74–1.23 and 0.83, 95% CI 0.55–1.23, respectively). The pooled risk ratio for bladder perforation was 0.13 (95% CI 0.05–0.34) in favor of en bloc resection. In randomized controlled trials, the differential rates of detrusor muscle presence (pooled RR 1.31, 95% CI 1.19–1.43) and of detectable muscularis mucosae (pooled RR 2.69, 95% CI 1.81-3.97) were more likely in patients receiving en bloc resection. Patients who underwent en bloc resection had a lower rate of residual tumor at repeat transurethral resection than those treated with conventional transurethral resection of bladder tumors in 1 randomized controlled trial and 3 observational studies (pooled RR 0.47, 95% CI 0.31–0.71). Conclusions: En bloc resection for bladder tumors seems to be safer, and to yield superior histopathological information and performance compared to conventional transurethral resection of bladder tumors. Despite the failure to improve the recurrence rate, the more accurate histopathological analysis is likely to improve clinical decision making and care delivery in nonmuscle-invasive bladder cancer.